The Overall assessment of the dynamics of dust load over the South-East European region - Lukaj, Edmond; Mandija, Florian; Vila, Floran (European Journal of Applied Sciences, 2021)
This paper presents a general view of the aerosol presence over the southeastern region of Europe. Analyses are presented in terms of the aerosol optical depth and fraction areas covered by dust plumes. The overall results show a relatively high dust load over the region, compared to the northern European regions. Almost similar results are obtained in the case of the other southern European regions, such is Iberian and Apennine Peninsulas. However, the annual cycles also clarify the differences on AOD maxima over this region in relation with other southern regions. The southeastern region is more affected by the dust intrusions especially during spring season whilst the south-western region is affected with more intensity during the summer season.